SARS-CoV-2 vaccination in the context of original antigenic sin - Marek Petráš; Ivana Králová Lesná (Taylor & Francis Group, 2022)
Immunological memory is the ability of the adaptive immune system to ensure a persistent protective effect after immunization. However, it can also be a limitation to building a sufficient level of protective antibodies specific to new mutations of the virus. It is imperative to bear this phenomenon (called "original antigenic sin") in mind and make every effort to overcome its inherent pitfalls when updating current and designing new vaccines.